Endovascular Treatment of Mycotic Aortic Aneurysms - Karl Sörelius; Kevin Mani; Martin Björck; Petr Šedivý; Carl‐Magnus Wahlgren; Peter Taylor; Rachel E. Clough; Oliver Lyons; Matt Thompson; Jack Brownrigg; Krassi Ivancev; Meryl Davis; et al. (2014)
Background— Mycotic aortic aneurysm (MAA) is a rare and life-threatening disease. The aim of this European multicenter collaboration was to study the durability of endovascular aortic repair (EVAR) of MAA, by assessing late infection–related complications and long-term survival. Methods and Results— All EVAR treated MAAs, between 1999 and 2013 at 16 European centers, were retrospectively reviewed. One hundred twenty-three patients with 130 MAAs were identified. Mean age was 69 years (range 39–86), 87 (71%) were men, 58 (47%) had immunodeficiency, and 47 (38%) presented with rupture. Anatomic locations were ascending/arch (n=4), descending (n=34), paravisceral (n=15), infrarenal aorta (n=63), and multiple (n=7). Treatments were thoracic EVAR (n=43), fenestrated/branched EVAR (n=9), and infrarenal EVAR (n=71). Antibiotic was administered for mean 30 weeks. Mean follow-up was 35 months (range 1 week to 149 months). Six patients (5%) were converted to open repair during follow-up. Survival was 91% (95% confidence interval, 86% to 96%), 75% (67% to 83%), 55% (44% to 66%), and 41% (28% to 54%) after 1, 12, 60, and 120 months, respectively. Infection-related death occurred in 23 patients (19%), 9 after discontinuation of antibiotic treatment. A Cox regression analysis demonstrated non-Salmonella–positive culture as predictors for late infection–related death. Conclusions— Endovascular treatment of MAA is feasible and for most patients a durable treatment option. Late infections do occur, are often lethal, and warrant long-term antibiotic treatment and follow-up. Patients with non-Salmonella–positive blood cultures were more likely to die from late infection.